2018
DOI: 10.1016/j.marpolbul.2018.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequences to assess the link between antibiotic and metal resistance in three coastal marine bacteria isolated from the mummichog gastrointestinal tract

Abstract: Antibiotic resistance is a global public health issue and metal exposure can co-select for antibiotic resistance. We examined genome sequences of three multi-drug and metal resistant bacteria: one Shewanella sp., and two Vibrio spp., isolated from the gut of the mummichog fish (Fundulus heteroclitus). Our primary goal was to understand the mechanisms of co-selection. Phenotypically, the strains showed elevated resistance to arsenate, mercury, and various types of β-lactams. The genomes contained genes of publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…That finding is in line with previously reported studies on mercury's impact on antibiotic-resistance selection (Skurnik et al, 2010). Lloyd et al (2018) showed that mercury-exposed fish microbiomes in the environment were highly susceptible to containing antibiotic-multiresistant bacteria, compared to unexposed controls. Coresistance due to mercury is apparently not new, since Wardwell et al (2009) showed that mercury-exposed indigenous bacterial strains in 2000-year-old sphagnum core samples had a multidrug-resistance phenotype.…”
Section: Heavy Metalssupporting
confidence: 92%
“…That finding is in line with previously reported studies on mercury's impact on antibiotic-resistance selection (Skurnik et al, 2010). Lloyd et al (2018) showed that mercury-exposed fish microbiomes in the environment were highly susceptible to containing antibiotic-multiresistant bacteria, compared to unexposed controls. Coresistance due to mercury is apparently not new, since Wardwell et al (2009) showed that mercury-exposed indigenous bacterial strains in 2000-year-old sphagnum core samples had a multidrug-resistance phenotype.…”
Section: Heavy Metalssupporting
confidence: 92%
“… 2017 ). A study assessing the link between antibiotic and metal resistance in marine bacterial isolates found that most resistance genes were chromosomally located and identified homologs of efflux pump genes which are commonly expressed to overcome pressure from heavy metals and may further contribute to resistant phenotypes (Lloyd, Nazaret and Barkay 2018 ). Similar results were obtained among bacterial communities sampled from hot springs (Jardine, Mavumengwana and Ubomba-Jaswa 2019 ).…”
Section: Amr and Pressure From Antibiotic Metabolites And Heavy Metalsmentioning
confidence: 99%
“…Burkholderia cepacia has been associated with lesions of the oral cavity of these animals including ulcerative stomatitis, and traumatic skin lesions. Shewanella putrefaciens has been regarded as a severe opportunistic bacterium [18,[39][40][41][42] and was described in one case of septicemia in green sea turtles (Chelonia mydas) with underlying fibropapillomatosis [12]. Citrobacter sp.…”
Section: Discussionmentioning
confidence: 99%